Circular Economy: A Comprehensive Review of Eco-Friendly Wollastonite Applications - Peres, Christiano Bruneli [UNESP]; Resende, Pedro R.; Nunes, Leonel J. R.; de Morais, Leandro Cardoso [UNESP] (MDPI, 2022)
The growing increase in greenhouse gases, especially carbon dioxide (CO2), by anthropogenic activities can be linked to extreme climate events, such as intensive droughts, floods, or hurricanes, and has led to several studies focused on reducing the concentration of this greenhouse gas in the atmosphere. Some technologies, such as carbon capture and storage (CCS), can potentially sequester billions of tons of CO2 per year. One of the promising methods is the use of carbon mineralization as a CCS methodology. For this approach, some minerals can be investigated, such as wollastonite, which can be obtained from agricultural waste recovery. One topic of interest in these studies is agriculture, demonstrating that it can play an important role in climate change mitigation. This work presents a critical review of the studies of rice waste use for potential synthesizing wollas-tonite as a path for CO2 storage, promoting the circular economy. Several works were analyzed and presented, addressing eco-friendly wollastonite use, such as in the cement industry, and they can contribute to a lower global warming potential. There is a promising way to explore, once there are few studies in the literature about CO2 capture and storage of wollastonite by carbon mineralization.
Keywords: Carbon capture and storage; Circular economy; Rice production; Wollastonite